Biomechanical Effects of Lateral Bending Position on Performing Cervical Spinal Manipulation for Cervical Disc Herniation: A Three-Dimensional Finite Element Analysis. (11th June 2018) - Huang, Xuecheng; Ye, Linqiang; Wu, Zixian; Liang, Lichang; Wang, Qianli; Yu, Weibo; Liang, De; Jiang, Xiaobing
Abstract : Background . Most studies report that the common position of cervical spinal manipulation (CSM) for treating symptomatic cervical disc herniation (CDH) is lateral bending to the herniated side. However, the rationality of lateral bending position on performing CSM for CDH is still unclear. Objective . The purpose of this study is to investigate the biomechanical effects of lateral bending position on performing CSM for CDH. Methods . A finite element (FE) model of CDH (herniated on the left side) was generated in C5-6 segment based on the normal FE model. The FE model performed CSM in left lateral bending position, neutral position, and right lateral bending position, respectively. Cervical disc displacement, annulus fiber stress, and facet joint stress were observed during the simulation of CSM. Results . The cervical disc displacement on herniated side moved forward during CSM, and the maximum forward displacements were 0.23, 0.36, and 0.45 mm in left lateral bending position, neutral position, and right lateral bending position, respectively. As the same trend of cervical disc displacement, the annulus fiber stresses on herniated side from small to large were 7.40, 16.39, and 22.75 MPa in left lateral bending position, neutral position, and right lateral bending position, respectively. However, the maximum facet stresses at left superior cartilage of C6 in left lateral bending position, neutral position, and right lateral bending position were 6.88, 3.60, and 0.12 MPa, respectively. Conclusion . Compared with neutral position and right lateral bending position, though the forward displacement of cervical disc on herniated side was smaller in left lateral bending position, the annulus fiber stress on herniated side was declined by sharing load on the left facet joint. The results suggested that lateral bending to the herniated side on performing CSM tends to protect the cervical disc on herniated side. Future clinical studies are needed to verify that.